2022
DOI: 10.3389/fpsyt.2022.958661
|View full text |Cite
|
Sign up to set email alerts
|

Microglia: Synaptic modulator in autism spectrum disorder

Abstract: Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by variable impairment of social communication and repetitive behaviors, highly restricted interests, and/or sensory behaviors beginning early in life. Many individuals with ASD have dysfunction of microglia, which may be closely related to neuroinflammation, making microglia play an important role in the pathogenesis of ASD. Mounting evidence indicates that microglia, the resident immune cells of the brain, are required for proper b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 171 publications
1
11
0
Order By: Relevance
“…Similarly, our study revealed the increased mean duration of grooming behavior, suggesting either a self-soothing mechanism or repetitive behavior [22,33]. Furthermore, microglial dysregulation is a prominent factor in the development of ASD [34]. These findings collectively suggest that microglial dysfunction leading to the suppression of Igf1 expression may contribute to the development of psychiatric disorders such as ASD.…”
Section: Discussionsupporting
confidence: 67%
“…Similarly, our study revealed the increased mean duration of grooming behavior, suggesting either a self-soothing mechanism or repetitive behavior [22,33]. Furthermore, microglial dysregulation is a prominent factor in the development of ASD [34]. These findings collectively suggest that microglial dysfunction leading to the suppression of Igf1 expression may contribute to the development of psychiatric disorders such as ASD.…”
Section: Discussionsupporting
confidence: 67%
“…This results in the downregulation of BLVRA in brain tumors, specifically, meningiomas and gliomas, with implications not yet elucidated with antioxidant status and chemoresistance in these tumor types [6,115]. Moreover, NFkB activation during hypoxic-ischemic injury [116] may contribute to the underlying cause of cerebral palsy [117][118][119][120] and autism spectrum disorders [121][122][123][124][125].…”
Section: Gsk3bmentioning
confidence: 99%
“…During inflammation, 2-AG, which is a ligand of endocannabinoid receptor, is released from various immune cells and induces neuroprotection through several mechanisms by binding to endocannabinoid receptor (Zou & Kumar, 2018 ). Microglial cells and astrocytes produce 2-AG in response to intracellular Ca +2 and glutamate receptor stimulation, which stimulates purinergic P2X7 receptor (Carrier et al, 2004 ; Hu et al, 2022 ). The ECS, specially CB2 receptor, mediates T and B lymphocytes proliferation, apoptosis, macrophage-mediated killing of sensitized cells, production of inflammatory cytokines by the inhibiting cyclic AMP/ Protein kinase A (PKA) pathways, migration of B cells, and cytokines induction.…”
Section: Microglial-endocannabinoid Signaling and Asdmentioning
confidence: 99%
“…The ECS, specially CB2 receptor, mediates T and B lymphocytes proliferation, apoptosis, macrophage-mediated killing of sensitized cells, production of inflammatory cytokines by the inhibiting cyclic AMP/ Protein kinase A (PKA) pathways, migration of B cells, and cytokines induction. Dendritic cells also have the capability to undergo cannabinoid-induced apoptosis due to their immunosuppressive properties (Do et al, 2004 ; Hu et al, 2022 ). So, ECS can be a crucial target for ASD therapies due to its anti-inflammatory and immunosuppressive effects.…”
Section: Microglial-endocannabinoid Signaling and Asdmentioning
confidence: 99%
See 1 more Smart Citation